2002
DOI: 10.1002/bit.10208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of immobilized penicillin G acylase using active‐site titration

Abstract: Penicillin G acylase from Escherichia coli was immobilized on Eupergit C with different enzyme loading. The activity of the immobilized preparations was assayed in the hydrolysis of penicillin G and was found to be much lower than would be expected on the basis of the residual enzyme activity in the immobilization supernatant. Active-site titration demonstrated that the immobilized enzyme molecules on average had turnover rates much lower than that of the dissolved enzyme. This was attributed to diffusion limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 13 publications
1
52
0
5
Order By: Relevance
“…Based on the literature and our results (Bosley and Peilow, 1997;Cao, 2005;Cruz et al, 2009;Janssen et al, 2002;Koops et al, 1999), we postulate here that three phenomena contribute to the observed catalytic activity maximum: 1.detrimental conformational changes of enzyme molecules upon adsorption on a solid (Bosley and Peilow, 1997;Koops et al, 1999), 2.beneficial interaction of adsorbed enzymes with neighboring enzyme molecules at increasingly "crowded" conditions, and 3. reactant and/or product diffusional limitations due to multi-layer deposition of the enzyme (Cao, 2005;Janssen et al, 2002;Koops et al, 1999). A more detailed mechanistic explanation of each situation is given below and schematically shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…Based on the literature and our results (Bosley and Peilow, 1997;Cao, 2005;Cruz et al, 2009;Janssen et al, 2002;Koops et al, 1999), we postulate here that three phenomena contribute to the observed catalytic activity maximum: 1.detrimental conformational changes of enzyme molecules upon adsorption on a solid (Bosley and Peilow, 1997;Koops et al, 1999), 2.beneficial interaction of adsorbed enzymes with neighboring enzyme molecules at increasingly "crowded" conditions, and 3. reactant and/or product diffusional limitations due to multi-layer deposition of the enzyme (Cao, 2005;Janssen et al, 2002;Koops et al, 1999). A more detailed mechanistic explanation of each situation is given below and schematically shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…Enzyme immobilization onto macro/micro surfaces is also typically required in order to enable their use in non-native applications such as in biosensors, environmental remediation materials, bioreactors, and other applied biotechnology fields [8,9]. Immobilizing enzymes onto planar surfaces can limit their performance due to multiple factors including the distortion of native protein configuration [10,11], steric hindrance, and slower diffusion rates of incident substrate toward the bulk surface [12,13]. To circumvent both the need to engineer enzymes and to eliminate the negative effects of enzyme immobilization on micro/macro surfaces, researchers have begun to utilize nanoparticles (NPs) as enzyme carriers.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods used to immobilize enzymes and three of the most common methods are physical adsorption, entrapment (encapsulation) and cross linking or covalently binding to a support (Janssen et al, 2002;Sheldon, 2007). For practical purposes, carrier beads with size falling into millimeter range are mainly used.…”
Section: Introductionmentioning
confidence: 99%